Dari Humanitarianism ke State Security: Sekuritisasi Pengungsi dalam Kebijakan Penerimaan Jepang - Salna Sari Ramadhan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
This study examines the systemic transformation of Japan’s refugee and immigration policy from 2021 to 2025, exploring how humanitarian paradigms have been superseded by state security considerations. The research aims to analyze how Japan constructs refugees as an existential threat to legitimize its restrictive reception regime, synthesizing Realism and Constructivism to explore the intersection of securitization, national interest, and identity. Methodologically, this paper employs a qualitative interpretive case study by integrating Ruth Wodak’s Discourse-Historical Approach (DHA) and Interpretive Process Tracing (IPT) to examine government texts, policy documents, and parliamentary debates. The findings reveal a profound policy asymmetry driven by intersubjective threat framing and institutionalized topoi (abuse, threat, law and order). Ukrainian displaced persons are positively categorized as evacuees (hinanmin) to align with G7 geopolitics, whereas traditional asylum seekers are pejoratively labeled as "repeated applicants" and framed as threats to public order, social harmony (wa), and ethnic homogeneity (tan’itsu minzoku). This discursive construction successfully legitimizes extraordinary measures within the 2023 amendment of the Immigration Control and Refugee Recognition Act (ICRRA), including the abolition of automatic deportation suspensions and the expansion of a surveillance state via alternative monitoring (kanri sochi). Ultimately, this study demonstrates that international norm compliance is deeply mediated by domestic cultural appropriateness (nihonjinron). It implies the necessity for future ethnographic research on grassroots impacts and suggests transparent asylum evaluation metrics aligned with non-refoulement principles.